Juvenile Nile Tilapia Fish Avoid Red Shelters - Maia, Caroline Marques [UNESP]; Alves, Nina Pacheco Capelini [UNESP]; Tatemoto, Patricia (Taylor & Francis, 2021)
Shelters are frequently used for fish rearing to improve welfare conditions. In this study, whether Nile tilapia prefers specific shelter colors was evaluated. Thus, fish preference for white, red, blue, green or yellow shelters was tested. A high variation of individual preference responses for the shelter colors among fish was found. Even so, while red shelter was clearly avoided by Nile tilapia, a clear-cut preference could not be concluded. Thus, avoiding red shelters for rearing Nile tilapia is recommended, assuming fish preference, or non-preference, as important elements considering welfare conditions. Moreover, individual variability should also be considered whenever possible.
Keywords: Animal welfare; avoidance; Nile tilapia; preference response